The strategic function of the P5-ATPase ATP13A2 in toxic waste disposal - de Tezanos Pinto, Felicitas (2017)
The P-type ATPase ATP13A2 protein was originally associated with a form of Parkinson´s Disease (PD)known as Kufor Rakeb Syndrome (KRS). However, in the last years it has been found to underlay variantsof neuronal ceroid-lipofuscinoses and hereditary spastic paraplegia. These findings expand the clinicaland genetic spectrum of ATP13A2-associated disorders, which are commonly characterized by lysosomaldysfunction. Nowadays it is well known that lysosomes are not merely related to the degradation andrecycling of cellular waste, but are also involved in fundamental processes such as secretion, plasmamembrane repair, signaling, energy metabolism and autophagy. The essential role of lysosomes in thesecellular processes has significant implications for health and disease. ATP13A2 is localized in lysosomesand late endosomes and its mutation leads to lysosome dysfunction, diminishes the exosome secretionand impairs autophagic flux. In this review, we first describe ATP13A2-associated disorders and theirrelation with the endolysosomal pathway. We then describe the ATP13A2-involvement in iron homeostasisand its potential linkage with new pathologies like cancer, and finally, we consider the putativerole of ATP13A2 in lipid processing and degradation, opening the interesting possibility of a broader roleof this protein providing protection against a variety of disease-associated changes affecting cellularhomeostasis.